Formulation of Partnership-Based MSME Financing Strategies in Islamic Banking: An Analytic Network Process Approach - Fitri Susanti Siregar; Sugianto; Rahmani, Nur Ahmadi Bi (Research Horizon, 2025)
Micro, Small, and Medium Enterprises are vital to Indonesia’s economy, particularly in North Sumatra, yet face challenges in accessing Islamic banking financing due to internal and external barriers. This study aims to formulate strategies to enhance partnership-based financing for these enterprises in Islamic banks. Using the Analytic Network Process, the research involved nine key informants from academia, regulators, and Islamic bank practitioners, employing in-depth interviews and pairwise comparison questionnaires to map problem elements and prioritize solutions. The findings identify the lack of bank staff competence in understanding the characteristics of Micro, Small, and Medium Enterprises as the primary internal barrier, while reliance on personal capital by business owners is the main external challenge. Priority strategies include staff training, multi-stakeholder collaboration, digital promotion of partner enterprises’ products, and policies for margin subsidies and collaboration forums. This research offers a strategic framework for inclusive, sharia-compliant financing policies to support regional economic growth. However, its focus on North Sumatra and limited informant sample may restrict broader applicability. The framework provides actionable guidance for policymakers and banks to strengthen financing ecosystems, fostering sustainable development for these enterprises.